Dark Fantasy in Neil Gaiman's Coraline: An Analysis of Formulaic Structure - Tarisa Badzlin Amajida; Setiawan, Ikwan; Wahyuningsih, Indah (Lakon : Jurnal Kajian Sastra dan Budaya, 2025)
In the early 21st century, technology paranoia, a negative aspect of technological growth, was prevalent, particularly in the United Kingdom. This social problem coincided with an increase in popular culture toward the consumption of fantasy fiction, with the dark fantasy subgenre being revived by Neil Gaiman's Coraline. This study explores Coraline through the lens of John G. Cawelti’s formula theory to reveal the strategies resulting in its significant societal appeal. This study analyzes the novella's intrinsic elements—plot, characters and characterizations, setting, and illustrations—to identify Coraline as a dark fantasy that effectively combines horror and fantasy formulas. The use of dark fantasy aligns with Cawelti's four hypotheses, functioning as a cultural reflection, cultural solution, cultural boundaries, and cultural innovation that addresses technology paranoia.